Political Communication Strategies through Video Podcast Campaign: A Case Study of Partai Perindo in Indonesia - Sompotan, Celly; Alvin, Silvanus (Pencerah, 2023)
This research presents an investigation into Partai Perindo's political communication strategies through video podcast campaigns, focusing on the impact of multi-platform digital campaigns that utilize both YouTube and Instagram. Adopting a qualitative approach with participant observation and interviews, the study highlights Partai Perindo's targeted efforts to engage millennial and Gen Z audiences, recognizing their influential role in the upcoming 2024 General Election. By leveraging YouTube's long-form content and Instagram's snackable teasers, Partai Perindo effectively captures diverse audiences' attention and fosters social consciousness, enhancing party electability and influencing policy decisions. The study underscores the significance of multi-platform strategies for political organizations seeking to engage young voters, promote civic participation, and address societal concerns, ultimately contributing to a more inclusive and responsive democratic society. Moreover, this research also proves that millennial and Gen Z voters get political information from social media as the main platform. On top of that, this research also offers valuable insights into contemporary political communication practices, with a focus on video podcasting and the integration of various digital platforms.